Non-obstructive CAD and Risk of All-cause Mortality in Middle-aged and Older Patients: A Nine-year Follow-up and Multicentre Study - Huang, Zengfa; Cao, Beibei; Zhu, Jinghang; Du, Xinyu; Yang, Yang; Li, Mei; Li, Zuoqin; Xiao, Jianwei; Huang, Jiong; Wang, Xiang (Current Medical Imaging, 2024)
Aim:We aimed to examine all-cause mortality risk in relation to the extent of non-obstructive coronary artery disease (CAD) by coronary computed tomography angiography (CTA) in Chinese middle-aged and older patients in a multicenter study with nine-year follow-up.Methods:This was a retrospective, observational, multicentre study. The study population consisted of 3,240 consecutive middle-aged and older patients (age ≥ 40 years) with suspected CAD who underwent coronary CTA between June 2011 and December 2013 at three hospitals in Wuhan, China. Patients were grouped according to CAD extent for the final analysis: no CAD, 1-vessel non-obstructive CAD, 2-vessels non-obstructive CAD, and 3-vessels non-obstructive CAD. The primary endpoint was all-cause mortality. Kaplan-Meier method and Cox proportional hazards regression models were used for analysis.Results:A total of 2,522 patients were included in the present analysis. Of these, 188 (7.5%) deaths occurred during the median 9.0 years (interquartile range 8.6–9.4) of study follow-up. The annualized all-cause mortality rate was 0.54 (95% CI: 0.44–0.68), 0.91 (95% CI: 0.68–1.21), 1.44 (95% CI: 1.01–1.93), and 2.00 (95% CI: 1.46–2.69) for the no CAD, 1-vessel non-obstructive CAD, 2-vessels non-obstructive CAD, and 3-vessels non-obstructive CAD group, respectively. Kaplan–Meier survival curves showed a significant increase in the cumulative events associated with the extent of non-obstructive CAD (P < 0.001). In multivariate Cox regression, after adjustment for age and sex, the presence of 3-vessels non-obstructive CAD was a significant predictor of all-cause mortality (HR 1.60, 95% CI: 1.04–2.45, P = 0.032).Conclusion:In this cohort of Chinese middle-aged and older patients undergoing coronary CTA, the presence and extent of non-obstructive CAD, compared to no CAD, were associated with a significantly greater nine-year risk of all-cause mortality. The present findings suggest the clinical importance of the stage of non-obstructive CAD and warrant investigation of the optimal risk stratification to improve outcomes among these patients.
Keywords: Cox regression